2010
DOI: 10.1038/hdy.2010.39
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of X-ray-generated floral mutants carrying deletions at the S-locus of distylous Turnera subulata

Abstract: To investigate the genetic architecture of distyly in Turnera subulata and test the hypothesis that a supergene determines distyly, we used X-ray mutagenesis to generate floral mutants. Based upon the crossing design, all progeny were expected to be short-styled. Of 3982 progeny screened, 10 long-styled mutants, one long homostyle and one short homostyle were recovered. Assays for molecular markers tightly linked to the S-locus showed that the mutants were missing 1-3 markers indicating they are deletion mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Heterostyly has arisen convergently in the genus Turnera, with some species exhibiting distyly in addition to homomorphic SI (Labonne et al, 2010). A series of experiments utilising hybrid crosses has uncovered a large S-linked region of over 1.6 megabases in three contigs containing several genes (Labonne and Shore, 2011), although it is not known whether these genes are functional in determining the SI phenotypes.…”
Section: Self-incompatibility and Heterostylymentioning
confidence: 99%
See 1 more Smart Citation
“…Heterostyly has arisen convergently in the genus Turnera, with some species exhibiting distyly in addition to homomorphic SI (Labonne et al, 2010). A series of experiments utilising hybrid crosses has uncovered a large S-linked region of over 1.6 megabases in three contigs containing several genes (Labonne and Shore, 2011), although it is not known whether these genes are functional in determining the SI phenotypes.…”
Section: Self-incompatibility and Heterostylymentioning
confidence: 99%
“…A series of experiments utilising hybrid crosses has uncovered a large S-linked region of over 1.6 megabases in three contigs containing several genes (Labonne and Shore, 2011), although it is not known whether these genes are functional in determining the SI phenotypes. X-ray-derived mutants show differing degrees of deletion of S-linked genes and a range of phenotypes affecting SI and flower morphology, indicating a multilocus architecture (Labonne et al, 2010). Although flower morphs are thought to be inherited as a single unit, there is no statistically significant decrease in recombination in the S locus compared with other loci, arguing against a genomic architecture such as an inversion, although it has been suggested that the S locus may reside in a collinear region with reduced recombination, such as near a centromere (Labonne and Shore, 2011).…”
Section: Self-incompatibility and Heterostylymentioning
confidence: 99%
“…Distyly has attracted the interests of prominent geneticists and evolutionary biologists, including William Bateson and Charles Darwin, in part because it is a striking example of convergent evolution of floral characters, physiology and possibly the underlying genetic architecture (Darwin 1877;Bateson and Gregory 1905;De Winton and Haldane 1935;Mather 1950;Ganders 1979;Barrett 1992). Although distyly is perhaps one of the most wellstudied breeding systems for plants displaying sexual polymorphism, the genes at the S-locus have not been discovered in any distylous species (Barrett and Shore 2008;Labonne et al 2010;Gilmartin and Li 2010).…”
Section: Introductionmentioning
confidence: 98%
“…It appears that this strategy is being exploited in at least three distylous genera namely, Primula, Turnera (Turneraceae) and Fagopyrum (Polygonaceae) where BAC libraries have been constructed for positional cloning of the S-locus (Nagano et al 2005;Li et al 2007;Yasui et al 2008;Labonne et al 2008;McCubbin 2008). Recently, both a high-resolution genetic map of the S-locus region of Turnera and a number of mutants carrying deletions at the S-locus of T. subulata have been generated as a valuable resource for positional cloning of genes determining distyly (Labonne et al 2009(Labonne et al , 2010.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation